IMPLEMENTASI 21ST CENTURY LEARNING DESIGN PADA KEMAMPUAN ICT CALON GURU SD - Iis Yeni Sugiarti; Dian Permana Putri; Ira Rahayu (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
Given the importance of ICT skills possessed by prospective elementary teachers to support learning activities and create a pleasant learning atmosphere. This study aims to analyze the ICT skills of prospective elementary teachers and design 21st CLD learning tools for prospective elementary teachers. This type of research is qualitative descriptive. The sample used was a random sampling of prospective elementary teachers who took basic and advanced literacy courses. Data collection techniques are in the form of ICT skills instruments, interviews, and observations. This study only uses three aspects, namely aspects of information and communication technology including the introduction of input and output devices, aspects of pedagogy including understanding literacy and numeracy materials and utilizing innovative media, as well as organizational and administrative aspects including understanding and mastering Google Workspace. The technology and information skills of prospective elementary teachers are by the 21st century learning needs that require digital technology.